2021
DOI: 10.3390/ani11030752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Immunobiotic Lactiplantibacillusplantarum N14 Fermented Rakkyo (Allium chinense) Pickled Juice on the Immunocompetence and Production Performance of Pigs

Abstract: Rakkyo (Allium chinense), is a Japanese leek that is primarily used to make a popular sweet or sour pickled dish. Lactic acid bacteria are often involved in the preparation steps of fermented pickles, which helps in the effective preservation of the natural bioactive compounds of fruits and vegetable, and thereby exert several health benefits including immunomodulation and growth performance. This work aimed to evaluate the in vivo effects of adding Lactiplantibacillus plantarum N14 fermented rakkyo pickled ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Additionally, probiotic bacteria can regulate immunomodulatory stimulation of the immune system [ 38 , 39 ] and regenerate intestinal mucosa [ 40 ]. Probiotics can increase the concentration of immunoglobulin [ 41 ] and augment the activity of macrophages and natural killer cells [ 42 ]. Probiotics can modulate the anti and pro-inflammatory cytokine production to control inflammation in the host [ 43 ].…”
Section: Role Of Probiotics On Animal Health and Nutritionmentioning
confidence: 99%
“…Additionally, probiotic bacteria can regulate immunomodulatory stimulation of the immune system [ 38 , 39 ] and regenerate intestinal mucosa [ 40 ]. Probiotics can increase the concentration of immunoglobulin [ 41 ] and augment the activity of macrophages and natural killer cells [ 42 ]. Probiotics can modulate the anti and pro-inflammatory cytokine production to control inflammation in the host [ 43 ].…”
Section: Role Of Probiotics On Animal Health and Nutritionmentioning
confidence: 99%
“…The in vivo study by Islam et al (2021) revealed that immunobiotic feeding resulted in significant positive health benefits when using rakkyo pickled juice fermented with L. plantarum N14 in pigs, thus increasing feed intake, efficiency, and carcass quality [31]. In addition, another study by Suda et al (2021) suggested that the immunobiotic L. delbrueckii subsp.…”
Section: Application Of Probiotics In In Vivo Studies For Pig Productionmentioning
confidence: 99%